Clinical correlates and outcome of the patterns of premature ventricular beats in Olympic athletes: a long-term follow-up study. (2nd June 2020) - Pelliccia, Antonio; De Martino, Lorena; Borrazzo, Cristian; Serdoz, Andrea; Lemme, Erika; Zorzi, Alessandro; Corrado, Domenico
Abstract: Background: The pattern of premature ventricular beats, as a clue to site of origin, may help identify underlying cardiac diseases. Aim: To assess the value of premature ventricular beat patterns in managing athletes with ventricular arrhythmias. Methods: Athletes with 50 or more isolated premature ventricular beats/24 hours, and/or multifocal and/or repetitive premature ventricular beats at baseline, and/or exercise, and/or 24-hour electrocardiograms were selected for this analysis. Premature ventricular beats were defined as 'common' (outflow tract or fascicular origin), or 'uncommon' (other morphologies and/or multifocal or repetitive). Results: From 4595 athletes consecutively examined, 205 (4%, 24.6 ± 6.9 years, 67% men) were included, 118 (58%) with uncommon and 87 (42%) with common premature ventricular beats. In particular, 81 (39%) showed complex patterns; 63 (31%) right/left ventricular outflow tract origin; 24 (12%) fascicular origin; 20 (10%) right bundle branch block pattern, intermediate/superior axis, wide QRS; and 17 (8%) left bundle branch block pattern, intermediate/superior axis. Uncommon premature ventricular beat patterns were predominant among men (62% vs. 38%; P  < 0.001) but not among women. Uncommon premature ventricular beats were equally prevalent in endurance, mixed and skill disciplines, but lower in power sports. Cardiac diseases were detected in 11 (5%), 10 with uncommon patterns. Over a 6-year follow-up, cardiac diseases occurred in four (0.6%/year), all with uncommon patterns. Overall, cardiac diseases at baseline and during follow-up were detected in 14/118 athletes with uncommon versus one/87 with common premature ventricular beats ( P  = 0.003). Conclusions: Evaluation of premature ventricular beat patterns in Olympic athletes identified cardiac diseases, requiring disqualification and/or follow-up, in 12% with uncommon versus 1% with common patterns. This result suggests that athletes with uncommon premature ventricular beat patterns should undergo comprehensive cardiac evaluation and/or serial follow-up, irrespective of gender or sporting discipline.